Effects of waves and currents on the siltation problem of Damietta harbour, Nile Delta coast, Egypt - ABO ZED, ABO BAKER.I. (Mediterranean Marine Science, 2007)
This study evaluates the effect of prevailing dynamic factors on the sedimentation process in Damietta Harbour along the Nile delta coast of Egypt. The monitoring program spanned the period between 1978 and 1999 and included measurements of waves, currents and bathymetric profiles. The evaluation was based on determination of erosion and accretion rates, current regime, sediment transport, wave characteristics and wave refraction. Results revealed that the predominant wave direction from N-NW sector (86 %) throughout the year is responsible for generation of a longshore eastward current. Less frequent waves from the N-NE sector generate an opposing longshore westward current. The refraction pattern for the prevailing wave direction indicates that the harbour and its navigation channel are located within a divergence of wave orthogonal and in an accretion sediment sink area. The annual net rate of littoral drift on the western side of the harbour is about 1.43 * 105 m3 (accretion), while the annual net rate of littoral drift on the eastern side is about 2.54 * 105 m3 (erosion). Currents fluctuate tremendously in speed and direction, especially during the winter months. Hence, sediment transport takes place in offshore, eastward, and onshore directions. Progressive vector diagrams show that the largest near bottom offshore, onshore and easterly net drift occurs during summer, spring and winter respectively. The onshore sediment transport generated during spring and summer plays an important role in the redistribution of eroded sediments during the winter. The overall study of dynamic factors indicated that the harbour site is characterized by eastern, western, offshore and onshore sediment movements. Therefore, the north-south orientation of the navigation channel, with its depth greater than the surrounding area, interrupts sediment drift from different directions and reduces the current speed. Consequently, the sediments sink within the navigation channel from different directions. The sources of sediments contributing to the siltation process of the harbour and its navigation channels are mainly derived from the Rosetta promontory, Burullus beaches, Damietta promontory and from offshore and the dumping area.